The The Influence of Teaching Prefixes and Suffixes In Context On Developing Students’ English Vocabulary at Sman 2 Garut - Yudi Kurniadi (KOMVERSAL, 2022)
Vocabulary through morphemes provides meaningful vocabulary acquisition skill. Students learn to guess the word meaning by looking for prefixes and suffixes in context. The students analyze prefixes and suffixes within the words. Then, the students analyze other context clues such as part of speech around the words. The purpose of this research is to uncover the significant difference between the influence of teaching prefixes and suffixes in context and without context toward students’ English vocabulary development. This research uses quantitative study in line with experimental method. This research was held in SMAN 2 Garut located at Jalan Guntur No. 3 Leles Garut. The population of this research is eight classes of students in the second grade of SMAN 2 Garut. The writer chooses two classes to be sample of the research, they are class XI IPA 1 as experimental group and class XI IPS 1 as the control group. The total numbers of the sample are 66 students. Pre-test and post-test are used to collect research data. Analisis butir soal pilihan ganda is used to test the validity of the data. To find out the reliability of the data, the writer uses split-half method as proposed by Suharsimi Arikunto ( 2009: 93). Because the data distribution is normal, t-test formula is used to analyze the data. Students’ diversity scores averages show that the experimental group gets 40 and the control group gets 30.15. It means that there is positive progress of the experimental group after having the treatment. Based on the data analysis, tcounted = 3.5 and ttable= 1.99. Because tcounted= 3.5 is out of Ho acceptation area, between ttable = -1.99 and 1.99, so that Ha is accepted. It means that Ha is accepted, there is significant difference of influence between teaching prefixes and suffixes in context and without context toward students’ English vocabulary development in the Second Grade Students of SMAN 2 Garut on ninety five percent (95%) significance level.